ANALISIS KEBUTUHAN RUANG PARKIR KENDARAAN BERMOTOR - Oktaviani Oktaviani; Revian Body; Nadra Mutiara Sari (Jurnal Teknologi Informasi dan Pendidikan, 2017)
The convenience of parking within campus can be an indicator of how well a campus facility is. So that can improve the credibility of the campus. The increase in infrastructure in the form of several new funding buildings from IDB (Islamic Development Bank) donor agencies is believed to be proportional to the increase in the number of students, lecturers, employees and the number of activities, so it is not worth the increased parking capacity. Therefore, it is necessary to calculate and analyze the number of parking needs of vehicles based on the SRP (Parking Space Unit) available on the Campus Universitas Negeri Padang to obtain parking characteristics such as parking accumulation, parking duration, turnover rate, parking capacity and parking index. Keywords: Parking Space Requirement, UNP Campus